Implementasi Polinomial dalam Menentukan Model Matematis Status Gizi Balita Berdasarkan Indeks Antropometri - Safrina, Lina (Sepren, 2026)
The nutritional status of children under five is very important to note because it is an indicator in measuring the degree of child health and economic development in various countries. Child growth charts that include weight-for-age (BB/U), length-for-age (PB/U) and weight-for-length (BB/PB) charts for boys and girls issued by the World Health Organization as a reference in monitoring children's nutritional status, tend to show polynomial growth patterns. The purpose of this study is to predict the mathematical model of nutritional status of toddlers based on anthropometric indices with a polynomial approach. Among the methods that can be used in matching data points with function graphs is polynomial interpolation. The more data points that are passed or known, the higher the degree of the polynomial formed. The coefficients of the polynomial are calculated using Newton's divided difference rule. Newton Polynomial Interpolation is obtained by entering the divided difference value into the polynomial interpolation equation. The calculation results from Newton’s polynomial interpolation equation is a mathematical model of toddlers nutritional status which is defined using a polynomial functions and a graphical visualization of the polynomial function of toddlers nutritional status is obtained which is close to the original child growth graph